The experience of healthcare workers to HIV pre-exposure prophylaxis (PrEP) implementation in low- and middle-income countries: a systematic review and qualitative meta-synthesis - Zhang, Liao; Song, Yuqing; Zheng, Xutong; Liu, Ying; Chen, Hong (Frontiers in Public Health, 2023)
Background The effectiveness of pre-exposure prophylaxis has been extensively documented. However, there are substantial gaps between the actual implementation of pre-exposure prophylaxis and the ideal goal, especially in low-and middle-income countries. Healthcare workers play critical roles in the pre-exposure prophylaxis implementation, and they have more multi-level experiences about the barriers of pre-exposure prophylaxis implementation and how to facilitate it. However, the evidence aiming to synthesize their experiences is limited. Objective This study aims to aggregate the healthcare workers’ experiences of providing pre-exposure prophylaxis in low-and middle-income countries, and find the barriers, facilitators, and recommendations of pre-exposure prophylaxis implementation. Methods The ENTREQ (Enhancing transparency in reporting the synthesis of qualitative research) statement was used to guide the design and reporting of this qualitative meta-synthesis. A comprehensive search was conducted from inception of databases to 16th March 2023 in four databases: PubMed, CINAHL Plus with Full Text, Embase, Web of Science. The quality appraisal was conducted using the Joanna Briggs Institute Critical Appraisal Checklist. JBI’s meta-aggregation approach was used to guide the data extraction and synthesis, and the JBI ConQual approach was used to evaluate the evidence level of the synthesized findings. Results Fourteen articles with good methodological quality were included in this review. A total of 122 findings were extracted and 117 findings with credibility ratings of “unequivocal” or “equivocal” were included in this meta-synthesis. The eligible findings were aggregated into 13 new categories and subsequently developed into 3 synthesized findings: the barriers, facilitators, and recommendations of pre-exposure prophylaxis implementation in low-and middle-income countries. The overall ConQual score of all three synthesized findings was rated as “low.” Conclusion This review aggregated the experience of health care workers implementing pre-exposure prophylaxis in low-and middle-income countries and we could focus on the following key points to promote the uptake of pre-exposure prophylaxis: improve knowledge about pre-exposure prophylaxis, create a supportive environment, address medication-related barriers, increase the human resources and financial investments, and diversify the providing models. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/. The protocol of this review has been registered in the International Prospective Register of Systematic Reviews (PROSPERO, CRD42023411604).